2014
DOI: 10.1016/j.matdes.2013.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tantalum content on the microstructure and mechanical behavior of cermets based on (TixTa1−x)(C0.5N0.5) solid solutions

Abstract: Titanium-tantalum carbonitride, (Ti,Ta)(C,N), based cermets with different Ti and Ta contents were prepared using a mechanically induced self-sustaining reaction and then densified using a pressureless sintering process. Complete microstructural and mechanical characterizations were performed on the materials, which revealed that the size of the carbonitride ceramic particle was significantly reduced when the Ta content was increased. The flexural strength and fracture toughness were measured using the ball on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 35 publications
5
23
0
Order By: Relevance
“…However, the reflections of Co, the presumed binder phase, were not observed in figure 1a after the MSR process. Instead, a broad peak centered at ~ 43º 2 was seen in all of the XRD diagrams, which as published previously [31], corresponds to an alloy containing Co and the other transition metals (Ti, Nb and Ta) introduced in the starting powder mixture.…”
Section: Synthesis Microstructure and Chemical Compositionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, the reflections of Co, the presumed binder phase, were not observed in figure 1a after the MSR process. Instead, a broad peak centered at ~ 43º 2 was seen in all of the XRD diagrams, which as published previously [31], corresponds to an alloy containing Co and the other transition metals (Ti, Nb and Ta) introduced in the starting powder mixture.…”
Section: Synthesis Microstructure and Chemical Compositionsupporting
confidence: 68%
“…Concerning the binder phase, it was observed that this phase was always composed of intermetallic compounds after HP sintering, as reported in previous studies of similar cermets sintered by pressureless (PS) methods [13,30,31] or spark plasma sintering (SPS) [29]. Based on the Ti-Co binary phase diagram [41] (table 3).…”
Section: Synthesis Microstructure and Chemical Compositionmentioning
confidence: 53%
See 1 more Smart Citation
“…Cermets combine the advantages of ceramics and metals [3]; the ceramic phase must mainly provide hardness and wear resistance, whereas the binder phase provides fracture strength and impact resistance [6]. For the hard component, other binary carbides, such as TaC, NbC, Mo 2 C, WC, HfC, VC and ZrC, are added to improve specific properties, for example, thermal shock resistance, hot hardness, chemical stability at high temperature, oxidation resistance and high-temperature creep resistance [7][8][9][10][11]. The binder phase can also contain other minor metallic components (Al, Cr, Mo, Fe, Mn, V or Ce) to support microstructure refinement, particulate dispersion, hardening of the binder and improvement of corrosion resistance [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of intermetallics in cermets, which precipitate during cooling, is not a new phenomenon [2,29,30] and has been associated with the excessive dissolution of the ceramic particles in the molten binder, causing Ti enrichment. Although some authors have shown that ductile intermetallic alloys, especially aluminides, are good candidates for binders because the mechanical properties of cermets can be retained at high temperature [31,32], the formation of brittle intermetallics during sintering, such as Ti x Ta 1-x Co 2 , can be extremely harmful for cermets, greatly damaging the fracture strength and toughness [8].…”
Section: Introductionmentioning
confidence: 99%